1967
DOI: 10.1111/j.1365-2672.1967.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Significance of Thermoduric Bacteria in Farm Milk Supplies: A Reappraisal and Review

Abstract: CONTENTS PAGE 26'i r i 1 hermoduric bacteria in farm milk supplies miportance of using a suitable brand of peptone in the plating medium, w liich should be at a pH of 7.5, while iiicubation should preferably be a t 28" for 96 h. The results of these findings should be incorporated in future revisions of standard techniques. Donovan & Vincent (1955) recommended the use of a double indicator (broniocresol purple and phenol red) agar medium for estimating the numbers and types of thermodurics, while Leali (1958) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Refrigerated farm bulk milk tanks do not provide a suitable environment for the multiplication of thermoduric bacteria, as most strains fail to grow a t temperatures < 10". Ten of the 12 tank rinses in the present survey contained < lo3 thermoduric organisms/ft2, compared with 84% of 104 tank rinses examined by Thomas et al (1967).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Refrigerated farm bulk milk tanks do not provide a suitable environment for the multiplication of thermoduric bacteria, as most strains fail to grow a t temperatures < 10". Ten of the 12 tank rinses in the present survey contained < lo3 thermoduric organisms/ft2, compared with 84% of 104 tank rinses examined by Thomas et al (1967).…”
Section: Resultsmentioning
confidence: 59%
“…According to Egdell et al (1950) thermoduric counts > 104/ft2 indicate a build-up of these organisms on farm dairy equipment due to inadequate cleaning and sterilization. Later, Thomas et al (1967) and Parry & Egdell (1969) showed that pipeline milking plants can contribute appreciable numbers of thermoduric bacteria to the milk when the temperature of the cleansing solution is too low. Furthermore, the role of pipeline milking plants as a major source of large numbers of thermoduric organisms in bulk-collected milk has been emphasized by Leali (1960) in Italy, La Grange & Nelson (1961) in the USA and Thomas (1972) in the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…The thermoduric corynebacteria have been studied extensively in relation to pasteurized milk. Thomas, Egdell, Clegg & Cuthbert (1950) and Thomas, Druce, Peters & Griffiths (1967) reviewed the literature on their incidence and heat resistant character, and also Jayne-Williams & Skerman (1966) made comparative studies on coryneform bacteria from milk and dairy sources. Kraft, Apes, Torrey, Salzer & da Silva (1966) found that of 15 genera isolated from turkey giblets, Corynebacterium was the most commonly isolated, the majority of which were unable to grow a t 5"; no data were given on their heat resistance.…”
Section: Discussionmentioning
confidence: 99%